If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3x + -10 = 0 Reorder the terms: -10 + 2x + -3x = 0 Combine like terms: 2x + -3x = -1x -10 + -1x = 0 Solving -10 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -1x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = 0 + 10 -1x = 0 + 10 Combine like terms: 0 + 10 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10
| 7x+2=4x+38 | | 5/8*6/1 | | 299.5+202.75+169.75= | | 1/8*5/1 | | Y=x^4-2x^2+1 | | 2(169.75)-40= | | 1/8*5/1*6/1 | | -r/1.3=7.4 | | 169.75+33= | | 1-(5c-2d)/(2c)+(c-2d)/(8c) | | H=-16t^2-25t+110 | | 1/2x+5=-1/2x | | 2x^2-6s+4= | | 2^-4/2^-5 | | 33/4x16 | | 2x+5x+6=0 | | (b^2/-2a^3)^2 | | t^2-5t+6= | | 375mL=L | | 2^-4a^3/2^-5a^-3=0 | | 6y+3y=6-12 | | (-4w+5)/-3=-7 | | 5a^2+9a-6=2a | | 8pq-3pq= | | 73/4+34/5 | | r^2+2r-8= | | 2x+7y=23 | | 2x-7y=23 | | 13x-8=5x | | -2/3-3/5 | | 6abc+(-11abc)= | | 3s-4b=23 |